A Case for Character : Towards a Lutheran Virtue Ethics - Biermann, Joel D. (Book collections on Project MUSE., 2014)
Equipped with a rich heritage detailing the content of human character, it would seem that Christianity is ideally positioned to address a culture where morality and personal character are set adrift. Contemporary Lutheranism has struggled with the place of morality and character formation, concerns often seen as at odds with the doctrine of justification. A Case for Character argues that Christian doctrine is altogether capable of encouraging character formation while maintaining a faithful expression of justification by grace alone.